Thematic Evaluation of Türkiye‑based Mobbing Research - Ergün, Hüsnü; Sari, Tamer (Journal of Qualitative Research in Education, 2025)
The current study aims to analyze the thematic evolution of mobbing research in Türkiye by utilizing theoretical frameworks to explore the systemic and individual factors influencing mobbing behaviour. Publication outputs, research trends, and thematic development of Türkiye-based mobbing research were examined using bibliometric methods. The Web of Science database was analyzed, and the Bibliometrix package developed for the R programming software language was used to analyse scientific productivity and scientific mapping analyses. The findings reveal that academic interest in mobbing has increased significantly, particularly since 2015. The motor themes of the 1999–2014 period focused on psychological violence, terror, and emotional abuse. During 2015–2019, research demonstrated how workplace bullying intersects with broader organizational dynamics, with emerging themes of job satisfaction, organizational commitment, and leadership styles. From 2015–2024, Türkiye-based mobbing research concentrated on the impact of COVID-19 pandemic-related isolation, remote work challenges, economic recessions, and their effects on employee turnover rates. The research reveals that cyberbullying has emerged as a new dimension of mobbing behavior in digital work environments. Notably, higher education institutions have become a significant focus area, with organizational cynicism and commitment emerging as important factors. In conclusion, mobbing remains a persistent workplace issue in Türkiye requiring continued academic and practical interventions to enhance workplace ethics and employee well-being.